2017
DOI: 10.1002/2017jg003855
|View full text |Cite
|
Sign up to set email alerts
|

The magic of fairy circles: Built or created?

Abstract: Fairy circles are rings of relatively dense grass in arid regions with sparse vegetation. The most famous examples are found in the Namib Desert. There has been an ongoing debate regarding the origin of these features, and a recent paper by Ravi et al. (2017, doi:10.1002/2016JG003604) sheds some light on this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…While there are multiple hypotheses for FCs origins, the two that enjoy current support are that dependent on faunal termite causation and on emergent vegetation patterning (Sahagian, ). Several studies have demonstrated that there are no direct observational data of past or present termite activities that support their potential role in the genesis of FCs in the central or southern Namib (Ravi et al, ; Tschinkel, , ) or in Australia (Getzin et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are multiple hypotheses for FCs origins, the two that enjoy current support are that dependent on faunal termite causation and on emergent vegetation patterning (Sahagian, ). Several studies have demonstrated that there are no direct observational data of past or present termite activities that support their potential role in the genesis of FCs in the central or southern Namib (Ravi et al, ; Tschinkel, , ) or in Australia (Getzin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The strongest environmental association of the Namib FCs is with mean annual precipitation, which ranges between approximately 50 and 150 mm (Cramer & Barger, 2013) and occurs where sparse grassland is dominated by Stipagrostis species on soils that are predominantly coarse-textured, aeolian-derived sands that have a high capacity for water and nutrient movement (Cramer et al, 2017;Ravi et al, 2017). The origin of these FCs in water-limited drylands has puzzled scientists for decades (Sahagian, 2017;van Rooyen et al, 2004). The hypotheses include (a) allelopathic influences of a plant that no longer occurs in FCs (Meyer et al, 2015;Theron, 1979); (b) seepage of carbon monoxide, hydrocarbons, or other volatiles from below ground that kills grass in regular patterns (Albrecht et al, 2001;Jankowitz et al, 2008;Naude et al, 2011); (c) an unspecified microbial effect (Eicker et al, 1982;Ramond et al, 2014;van der Walt et al, 2016); (d) faunal removal of grasses by termites (Becker & Getzin, 2000;Juergens, 2013;Moll, 1994;Vlieghe et al, 2015) or detrimental influence on grasses by ants (Picker et al, 2012); and (e) self-organized emergent vegetation patterning arising from competitive and facilitative interactions between grasses (Cramer et al, 2017;Cramer & Barger, 2013;Getzin et al, 2015aGetzin et al, , 2015bGetzin et al, , 2016Ravi et al, 2017;Tschinkel, 2012;van Rooyen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fairy circles differ from these trivial insect‐created gaps by having an exceptionally distinct and rare spatial pattern and by not having a clear causal agent, making them a long‐standing, mysterious landscape scale phenomenon (van Rooyen et al. , Tschinkel , Sahagian ). The rare Namibian and Australian FCs were precisely described with scale‐dependent spatial statistics (Getzin et al.…”
Section: Discussionmentioning
confidence: 99%
“…Fairy circles are not just ordinary grassland gaps which are indeed common in large parts of Australia, North America, and elsewhere. Fairy circles differ from these trivial insect-created gaps by having an exceptionally distinct and rare spatial pattern and by not having a clear causal agent, making them a long-standing, mysterious landscape scale phenomenon (van Rooyen et al 2004, Tschinkel 2012, Sahagian 2017. The rare Namibian and Australian FCs were precisely described with scale-dependent spatial statistics (Getzin et al 2015b(Getzin et al , 2016a, showing that these grassland-gap patterns are unambiguously defined by two fundamental spatial properties: an extraordinary degree of spatial ordering (extreme regularity) at small scales r < 50 m and homogeneity at large scales.…”
Section: Drone Survey and Spatial Pattern Analysis-hypothesismentioning
confidence: 99%
See 1 more Smart Citation